The influence of message framing and time metaphors in green advertising on consumer effects: an examination based on the mediating role of approach-avoidance motivation - Dong, Mingfang; Cao, Danyang; Liu, Tianli (Frontiers in Psychology, 2025)
ObjectivesThere is currently a discrepancy between consumers' understanding and practice of green consumption, resulting in inadequate levels of engagement. It is crucial for enterprises to design persuasive green advertisements to enhance consumers' willingness to make green purchases.MethodologyThis research employs the perspective of time movement and the S-O-R theoretical model. Two scenario experiments were conducted alongside a questionnaire survey to examine the effects of green advertising message framing (gain vs. loss), time metaphors (ego-moving vs. time-moving), and approach-avoidance motivation on consumers' willingness to make green purchases.FindingsWhen green advertisements utilize a gain-framing, ego-moving metaphor effectively enhance consumers' willingness to purchase. Conversely, loss-framing paired with time-moving metaphor better promote green consumption behaviors. Approach and avoidance motivations mediate the effects between message framing and time metaphors.ConclusionEnterprises should consider the matching effects of different information types when designing green advertisements. Specifically, aligning gain-framing with ego-moving metaphor and loss-framing with time-moving metaphor can significantly enhance consumer purchase intentions. Additionally, marketers should focus on consumers' psychological motivations, as approach-avoidance motivation affects the impact of advertising message combinations on purchasing willingness.ImplicationsThe findings elucidate the psychological pathways influencing consumers' green purchasing decisions, assisting enterprises in optimizing advertising message strategies and offering theoretical and practical recommendations for effective green advertising design.